The Commensal Microbiota Drives Immune Homeostasis - Arrieta, Marie-Claire; Finlay, Barton B. (Frontiers in Immunology, 2012)
For millions of years, microbes have coexisted with eukaryotic cells at the mucosal surfaces of vertebrates in a complex, yet usually harmonious symbiosis. An ever-expanding number of reports describe how eliminating or shifting the intestinal microbiota has profound effects on the development and functionality of the mucosal and systemic immune systems. Here, we examine some of the mechanisms by which bacterial signals affect immune homeostasis. Focusing on the strategies that microbes use to keep our immune system healthy, as opposed to trying to correct the immune imbalances caused by dysbiosis, may prove to be a more astute and efficient way of treating immune-mediated disease.